PENGARUH PIJAT KAKI DAN RENDAM AIR HANGAT CAMPUR KENCUR TERHADAP EDEMA KAKI FISIOLOGIS PADA IBU HAMIL TRIMESTER III - dwi handayani; Raisha Octavariny; Ika Nur Saputri (JURNAL ILMIAH DHDT - KEBIDANAN, 2020)
Physiological foot edema is found in about 80% of pregnant women. This occurs because of uterine pressure that inhibits venous return. Physiological foot edema if left untreated can cause discomfort, feeling heavy and cramping at night. This study aims to analyze the effect of foot massage and soaking mixed with warm water on pregnant women in the clinic of Nining Pelawati sub-district Lubuk Pakam, Deliserdang Regency. The type of research used in this study is the type of Quasy Experimental research with One Group Pre-Test and Post-test design. erian that has been determined by the researcher. The population in this study were all trimeter III pregnant women who experienced physiological foot edema, the sample in this study was 10 respondents with purposive sampling technique. Based on the results of the study, it was found that prior to the intervention of the mother with a degree of severe edema of 50% and a moderate degree of 50%, while after the intervention obtained a degree of edema was 50% and mild 50%. Based on these results the p-value of 0.002 <0.05 was obtained. This means that there is an effect of foot massage and soaking mixed with warm water on physiological foot edema in third trimester pregnant women .